Tarâduf Analysis in Khulâshoh Nûrul Yakin Juz 1 Part 1/ Analisis Tarâduf dalam Khulâshoh Nûrul Yakin Juz 1 Bagian 1 - Supardi, Adi; Burhanuddin, Muhammad Wildan (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2021)
This research focuses on the analysis of the meaning field on a series of word synonyms nasaba-nasala, hadhona-kafala, and syarofa-sâda, so that the meaning found can facilitate contextualization in translating sentences.  This study aims to look at the field of meaning of tarâduf in the analysis of the words nasaba-nasala, hadhona-kafala, and syarofa-sâda in the Khulâshoh Nûrul Yakin book so that the field of meaning of tarâduf (word synonyms) can form a relationship between several words into a similarity of meaning. The research method used a content analysis study with a qualitative descriptive approach in the literature of the book Khulâshoh Nûrul Yakin. The results show that the lexical meaning of nasaba-nasala is descent, the meaning of hadhona-kafala is to take care, and syarofa-sâda is noble. Meanwhile, the situational meaning of the context results in the result that nasaba is hereditary due to family biological factors, while nasala is hereditary due to ethnicity and state factors, then hadhona is taken care of due to breastfeeding custody, while kafala is taking care of, caring for family responsibilities, then syarofa is the glory that the personal business factor of the actor of the group is obtained, while sâda is the glory because of the descent of the group or tribe.